2016
DOI: 10.1002/jat.3326
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiles in a monkey testicular injury model induced by testicular hyperthermia

Abstract: To characterize microRNAs (miRNAs) involved in testicular toxicity in cynomolgus monkeys, miRNA profiles were investigated using next‐generation sequencing (NGS), microarray and reverse transcription‐quantitative real‐time‐PCR (RT‐qPCR) methods. First, to identify organ‐specific miRNAs, we compared the expression levels of miRNAs in the testes to those in representative organs (liver, heart, kidney, lung, spleen and small intestine) obtained from naïve mature male and female monkeys (n = 2/sex) using NGS analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The most abundant known miRNA was miR‐143‐3p, with 28.36% of total high quality counts of perfect matched reads, and the second most abundant known miRNA was miR‐21, with 16.16% of total high quality counts of perfect matched reads (Supporting Information Table S3). miR‐143 and miR‐21, in our study, were also found to be relatively highly expressed in mouse spermatogenic cells (Ro, Park, Sanders, McCarrey, & Yan, ), monkey testis (Sakurai et al, ), and porcine testis (Lian et al, ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The most abundant known miRNA was miR‐143‐3p, with 28.36% of total high quality counts of perfect matched reads, and the second most abundant known miRNA was miR‐21, with 16.16% of total high quality counts of perfect matched reads (Supporting Information Table S3). miR‐143 and miR‐21, in our study, were also found to be relatively highly expressed in mouse spermatogenic cells (Ro, Park, Sanders, McCarrey, & Yan, ), monkey testis (Sakurai et al, ), and porcine testis (Lian et al, ).…”
Section: Resultssupporting
confidence: 69%
“…**p < 0.01; # p < 0.05; ## p < 0.01, according to one-way ANOVA with a least significant difference (LSD) test. NC: negative control [Color figure can be viewed at wileyonlinelibrary.com] monkey testis (Sakurai et al, 2016), and porcine testis (Lian et al, 2012).…”
mentioning
confidence: 99%
“…To test whether miRNA-targeting can restrict ZIKV replication in mouse testis, we replaced scr sequences in 2×scr with sequences complementary to testis-specific miRNAs mir-202–5p and mir-449a-5p [Fig. 2a 2830 ], generating 2×202(T) and 2×449a(T) viruses, respectively (Fig. 2b, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma miRNA Analysis miRNA analysis was conducted by RT-qPCR as previously described (Sakurai et al 2016). Briefly, whole blood samples were collected from the inferior vena cava of anesthetized animals into EDTA 2K-containing tubes at necropsy.…”
Section: Pathologymentioning
confidence: 99%